Development Of Pai Learning Methodology (21st Century Learning Model) - Fradhani Rihhadatul Aisy Rambe; Risma Sulistia Aini; Kalayo Hasibuan (Yayasan Rahmat Islamiyah, 2025)
21st century learning is designed to prepare students to face the challenges of the complex globalization era. This research discusses creativity, innovation, and collaboration-based learning models as strategies to improve 21st century skills, which include critical thinking, communication, collaboration, and creativity (4C). Using a literature study-based qualitative approach, this research explores the implementation of learning models such as Discovery Learning, Inquiry Learning, Collaborative Learning, and Project-Based Learning (PjBL) in the context of Islamic Religious Education (PAI). These learning models are able to improve students' understanding of materials, such as zakat, through real projects that are relevant to daily life. The findings show that this approach is effective in developing students' creative, innovative and teamwork skills, while utilizing technology as a supporting tool. This research recommends strengthening project-based learning methods and technology integration to prepare students for future challenges.